(untitled) - Gray, Paul R. (New York, 1993)
Presents a detailed, comparative treatment of analog integrated circuit analysis and design, combining bipolar, CMOS, and BiCMOS analog integrated-circuit design. This edition expands its coverage of a few important technologies and techniques, including increased emphasis on CMOS circuits; a new chapter on fully differential amplifiers and common-mode feedback; new material on feedback circuit analysis using return ratio in addition to the two-port feedback analysis; and new coverage of two-stage MOS op-amp compensation, single-stage op amps, and nested Miller compensation. Includes a number of open-ended design problems, many of which make extensive use of SPICE. Of likely utility as a text for students and as a reference for practicing engineers. Annotation c. Book News, Inc., Portland, OR (booknews.com).
Keywords: Linear integrated circuit,Metal oxide semiconductors; Computer-aided designs,Computer-aided designs